THE SIGNIFICANCE OF ARISTOTLE AND PLATO'S IDEAS IN THE PHILOSOPHY OF ABU NASR FARABI (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article reflects the relationship between the philosophy of Abu Nasr Farabi, one of the great figures of Eastern philosophy, with the ideas of Aristotle and Plato, ancient Greek philosophers. In the article, the views of Farabi, who embodies both materialist and idealist ideas, are analyzed in comparison with Greek philosophers, including Aristotle's materialism and Plato's idealism. In the article, it is emphasized that Farobi brought the Greek philosophical ideas to the philosophy of the Muslim East by deeply studying Greek science and writing commentaries on the works of Greek philosophers, thereby bringing about a mutual compromise between Greek philosophy and Islamic philosophy.